Psychosocial impacts in adult hearing-impaired and their spouses - Tengku Zam Zam, Tengku Zulaila Hasma; Dzulkarnain, Ahmad Aidil Arafat; Rahmat, Sarah; Jusoh, Masnira (2017)
Background and purpose of study: Spouse is the closest family member to the hearing-impaired patients and past literature has shown that hearing impairment resulted to poor emotional-wellbeing in both parties. Despite the reports on psychosocial effects in both spouse and patients, little attention has been paid to determine the relationship of both (spouse and patient) psychosocial consequences. Therefore, this study aims to investigate the psychosocial impacts of hearing impairment to the hearing-impaired adults and correlation to their spouses’. Methods: Two self-reported questionnaires, Malay Hearing Handicap Inventory for Adult (HHIA-M) and Malay Significant Other Scale for Hearing Disability (SOSHEAR-M) were used to investigate the existence and the relationship of self-perceived disability among adult hearing impaired and their spouses. Twenty-six couples participated in the survey using those two validated questionnaires. Result: SOSHEAR-M score (median=11.06) was significantly higher than HHIA-M score (median=8.00) suggesting slightly higher impact of hearing loss towards spouse than the hearing impaired sufferers . Despite only slight different in the psychosocial effect between these two groups, Spearman correlation found no association between the HHIA-M scores and SOSHEAR-M scores. Conclusion: This study concluded that psychosocial impacts of hearing impairment were also experienced by their spouses. Above all, some spouses were more affected as compared to their hearing-impaired partners. To avoid detrimental effect of hearing loss to the spouse it is therefore important to measure their psychosocial impact from their partner hearing impairment and at the same time to uniquely manage their problems by including them in the hearing rehabilitation program.